Harmonizing trade laws in South Asia: a future thought - Md. Habib Alam (Penerbit Universiti Kebangsaan Malaysia, 2019)
International trade law is one of the key factors for economic development for a country or regional development. The South Asian Association for Regional Cooperation (SAARC) is one of the Southern Associations which consists of 8 countries. SAARC follows the same trend of “Sustainable trade.” Sustainable trade depends on the globalization of trade. Globalization of trade depends on uniformity. Uniformity may be two types, regional uniformity (i.e. SAARC) and multi-regional uniformity (i.e. a combination of more than one regional uniformity, like CISG). This research is on SAARC (i.e. regional uniformity) to harmonize the trade laws. SAARC states have different treaties (i.e. bilateral treaties, oral agreements, business usages, may have different publicly known or unknown agreements linking with arbitration etc.). These different instruments or laws may give rise to conflicts of laws within SAARC states. Judges of different jurisdictions of SAARC may interpret in different ways and complexity in trade laws will increase. It will help involving more expenditure (i.e. long procedure to solve the disputes, hiring foreign lawyers, expertise expenditure etc.). The main objective of this research is as to how we can harmonize the trade laws within the SAARC region by complying with international standard in every jurisdiction of SAARC states. This research provides an idea that we need to form a new uniform sale law like CISG for sustainable trade within SAARC states.